2017
DOI: 10.26822/iejee.2017236114
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Teachers Conceptions and Practices of Formative Assessment Scale into Turkish Culture and a Structural Equation Modeling

Abstract: The purpose of this study was to adapt Teachers' Conceptions and Practices of Formative Assessment Scale (TCPFS) based on the Theory of Planned Behavior (TPB) into Turkish culture and apply the TPB to examine teachers' intentions and behaviors regarding formative assessment. After examining linguistic validity of the scale, Turkish scale was applied to 400 primary school teachers in Turkey. Confirmatory factor analysis (CFA) was administered for the construct validity. The results showed that the model had fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 57 publications
1
10
1
Order By: Relevance
“…Moreover, the result showed that the APMT model had a good fit of CFA. These results were consistent with several studies aimed to construct scales of teachers' assessment practices by using CFA, such as Hasnida et al (2018), Karaman and Şahin (2017) and Ling et al (2012).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the result showed that the APMT model had a good fit of CFA. These results were consistent with several studies aimed to construct scales of teachers' assessment practices by using CFA, such as Hasnida et al (2018), Karaman and Şahin (2017) and Ling et al (2012).…”
Section: Discussionsupporting
confidence: 92%
“…"I have given…provided…", "…enables my students…" signified improved self-esteem towards implementing FA. Their efforts to utilize FA practices have shown their certainty and control in conducting it (Karaman & Sahin, 2017). Their handling of tasks and activities revealed their high confidence in corresponding positively to their actual formative assessment practices inside the classroom.…”
Section: Self-efficacy (Sef)mentioning
confidence: 99%
“…Self-efficacy can positively or negatively influence people's thoughts (De Smul et al, 2018) and may affect teachers' emotions at work and the conduct of FA in their classes. This construct associated with teachers' confidence and control in implementing FA (Karaman & Sahin, 2017) could provide important information to the assessment practice.…”
Section: Self-efficacy (Sef)mentioning
confidence: 99%
“…The authors concluded that the TPB may not be able to capture the specificity of individualized support. Yan and Cheng (2015) and Karaman and Sahin (2017) conducted the only two quantitative studies about the determinants of formative assessment under the framework of the TPB. Yan and Cheng (2015) developed the Teachers' Conceptions and Practices of Formative Assessment Scale (TCPFS), a 40-item instrument based on an extended version of the TPB.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%